Shielding Calculation for Nuclear Medicine Services - Madero Ramirez, Diego Armando; Orejuela, Diego Mauricio; Plazas De Pinzon, María Cristina (TECCIENCIA, 2017)
Nuclear medicine is a medical specialization that uses radioactive materials injected into the body to diagnose and treat human diseases. The use of different radionuclides and high amounts of radioactive materials makes it necessary for the facilities where these procedures are conducted to evaluate the corresponding shielding to comply with the design dose limits of a facility and avoid radiological accidents as recommended and accepted in international publications, like the International Commission on Radiological Protection (ICRP) and the National Council on Radiation Protection and Measurements (NCRP). This work compares two methods to calculate the shielding necessary to guarantee que las medicine service zones be safe from ionizing radiations. The first method consists in calculating the transmission factor B to find the thickness of the material necessary to protect the zone of interest, this factor is calculated by bearing in mind the occupancy factors, workloads, use factor, and the design objective dose limit. Upon obtaining the transmission factor B, half value layer (HVL) or tenth value layer (TVL) tables are used for each construction material, obtaining the thickness of the material. The other method is the calculation of is the calculation of rates of exposure through the air Kerma rate constant, then the XCOM databases are used, which were developed by the National Institute of Standards and Technology (NITS) to obtain the attenuation coefficient, used in the law of exponential attenuation; finally, the necessary thickness of the material is obtained to reach the design objective. Finally, the principal differences between both methods are shown and an analysis is performed of the shielding optimization, seeking to set criteria to make recommendations to nuclear medicine services on optimal shielding.